Land, Property & Wealth Owners, as a Comparison of Public Policy & Government History - Dr. James E. Curtis, Jr. (Modern Perspectives in Economics, Business and Management Vol. 9, 2021)
This study presents one of the first national studies that combines the migration and race of the economic experiences of free blacks, with an extended analysis of antebellum wealth inequality. In doing so, analyze economic asymmetry among early blacks and whites in the United States of America. For the data analysis, study used information from the Integrated Public Use Microdata Sample (IPUMS). The present results of informative property ownership and wealth ratios. This study finds that economic differences among ethnic groups, as measured by differences between early blacks and whites, are intertwined with asymmetrical freedoms.